2015
DOI: 10.1039/c4md00333k
|View full text |Cite
|
Sign up to set email alerts
|

The status of the lysophosphatidic acid receptor type 1 (LPA1R)

Abstract: Lysophospholipids are lipid molecules that are receiving growing attention because, in addition to their structural function in the cell membrane, they are now regarded as important regulators for diverse biological functions through activation of specific receptors. These receptors have been characterized during the last two decades as G protein-coupled receptors (GPCRs) and, among them, two families stand out: lysophosphatidic acid (LPA 1-6 ) and sphingosine 1-phoshate (S1P 1-5 ) receptors. Despite their int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 88 publications
0
17
0
Order By: Relevance
“…We found that neither autotaxin nor LPAR antagonists attenuated LPC‐induced toxicity. In addition, most of the LPAR1–6 signaling is sensitive to either pertussis toxin or Rho signaling mechanisms (Gonzalez‐Gil et al, ; Lee, Rivera, Gardell, Dubin, & Chun, ), which also did not attenuate LPC‐induced injury (Figure ).…”
Section: Resultsmentioning
confidence: 98%
“…We found that neither autotaxin nor LPAR antagonists attenuated LPC‐induced toxicity. In addition, most of the LPAR1–6 signaling is sensitive to either pertussis toxin or Rho signaling mechanisms (Gonzalez‐Gil et al, ; Lee, Rivera, Gardell, Dubin, & Chun, ), which also did not attenuate LPC‐induced injury (Figure ).…”
Section: Resultsmentioning
confidence: 98%
“…Cancer cells have a higher LPA receptor content on their cell surface compared to normal and benign cells and a downregulated expression of LPPs [ 128 ]. Therefore, targeting LPA signaling through these components is currently under study and constantly reviewed [ 4 , 127 , 129 – 132 ]. In this section, we summarize some of the drugs studied regarding ATX inhibition and LPA receptor antagonism ( Table 1 ).…”
Section: Targeting Autotaxin-lpa Axis For Cancer Therapymentioning
confidence: 99%
“…LPA activates at least six G-coupled protein receptors (LPA 1–6 ) stimulating different signaling pathways through heterotrimeric G proteins such as G i/0 , G 12/13 , G q/11 , and G s . The outcome of LPA signaling is dependent on cellular context and impacts on biological processes such as wound healing, differentiation, neurogenesis, and survival, to name a few [ 4 ]. Due to its small structure, LPA is water soluble and concentrations > 5 μ M have been reported in serum; concentrations < 1 μ M have been found in other biofluids such as plasma, saliva, follicular fluid, cerebrospinal fluid, and malignant effusions [ 5 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…To test this hypothesis, immunoprecipitation analysis was performed in shCon, shIFT88, and shKIF3B astrocytes transiently overexpressing 3xFLAG-LPAR1. Based on sequence similarity, LPAR1 is predicted to interact with Gαi, Gαq, and Gα12 ( 19 ). No interaction was detected between LPAR1 and Gαs.…”
Section: Resultsmentioning
confidence: 99%
“…LPA acts through binding of heterotrimeric G-protein coupled receptors (LPAR1-6). It was previously reported that LPAR1 can signal through Gαi, Gα12, and Gαq family members ( 18 , 19 ). LPA stimulates cell proliferation in astrocytes ( 20 ) and cancer cells ( 21 ).…”
Section: Introductionmentioning
confidence: 99%